Antioxidant and Antimicrobial Activity of Polyphenols Extracted after Adsorption onto Natural Clay “Ghassoul” - Safae Allaoui; Mohammed Naciri Bennani; Hamid Ziyat; Omar Qabaqous; Najib Tijani; Najim Ittobane; Mohammed Barbouchi; Aziz Bouymajane; Fouzia Rhazi Filali (Journal of Chemistry)
Natural polyphenols contained in olive mill wastewaters (OMW) have been usually associated with great bioactive properties as “antioxidants”. In this work, we recovered the polyphenols after adsorption onto natural clay “ghassoul” by different solvents: water, ethyl acetate, and methanol (PPW, PPA, and PPM, respectively) to avoid environmental pollution. Also, we tested the antioxidant activity of the extracted polyphenols by two methods: 1,1-diphenyl-2-picrylhydrazyl (DPPH) and total antioxidant capacity (TAC). Then, we analyzed antimicrobial activity by the microdilution technique to determine at the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC). The OMW of the Fez-Meknes region has a very acidic pH, considerable amounts of mineral matter, and a high concentration of polyphenols and organic content. The results of the test from DPPH showed good antiradical potential for polyphenols extracted with water, but the TAC showed an important capacity for all extracts unless PPA. The antibacterial activity is not the same on the four bacteria studied (Escherichia coli, Salmonella sp, Staphylococcus aureus, and Enterococcus faecalis), and all extracts inhibit most tested germs that do not have the same MIC and the same sensitivity. Only the PPW showed the minimum bactericidal concentration (MBC) that is equal to 0.290 mg/mL for Salmonella sp and Staphylococcus aureus, which confirms that the extraction by water of the adsorbed polyphenols is an original solution to recover the polyphenols and also to obtain a natural phenolic antioxidant which can be used in the pharmaceutical, nourishment, and cosmetic industry.